Prediction of tar yield produced from devolatilisation of empty fruit bunch in a fluidised-bed reactor using pseudo-equilibrium model - Md Said, Mohamad Syazarudin; Ahmed, A.M.A.; Ali, Salmiaton; Yaw, Thomas Choong Shean; Wan Ab Karim Ghani, Wan Azlina (Elsevier, 2023)
In this work, a pseudo-equilibrium model (PEM) is developed for prediction of yield and product from devolatilisation of empty fruit bunch (EFB). The yield of individual species (H2, CO, CO2, CH4, bio-oil, tar, and char) from the primary decomposition of EFB is expressed empirically. Subsequently, they are the inputs to the secondary reaction region. In the secondary reactions zone, the water-gas shift reaction (WGSR) is treated under equilibrium conditions, but kinetically modified by a factor to predict the concentration of the four gases (H2, CO, CO2, and H2O) which participated in this reaction. Meanwhile, the methane, bio-oil and tar are modelled separately in a purely kinetic environment by applying a plug flow reactor (PFR) model to estimate the conversion of both species. The model is further to investigate the effects of changes in the operating conditions of devolatilisation such as temperature and carrier gas flow rate. The results showed a good prediction for tar yield with low root mean square (RMS = 0.003) compared to experiments, and conversion (59.7%) compared to experiments (51.5%) at 850 °C. A sensitivity analysis for the pyrolysis model was conducted to investigate the effects of process temperature and nitrogen gas flowrate. Tar yield was significantly reduced at high temperatures. Meanwhile, the change of nitrogen flowrate resulted in slight increase of tar yield. Reasonable predictions were obtained for other products.